Nutritive value of forages as affected by soil and climatic differences - Richardson, D.; Banbury, Evans E.; Erhart, A.B.; Davidson, F.R.; Williams, G.; Smith, E.F.; Loper, D.C.; Harbers, L.H.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
It is generally thought that performance of cattle may differ in various parts of the state due to location, soil, climate, rainfall and/or feed produced. This project is an attempt to determine whether such differences exist and, if so, to measure them.
Keywords: Beef; Sorghum silage; Performance; Alfalfa